STUDY OF CALCIPOTRIOL BETAMETHASONE OINTMENT IN THE TREATMENT OF PATIENTS WITH REFRACTORY CHRONIC ECZEMA - JU, MEI; XU, AIE; DUAN, YIQUN; WEN, HAI; LI, TIENAN; XU, LIMIN; CHEN, KUN; GU, HENG (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Chronic eczema is an inflammatory-immune disease of the skin, with the characteristics of skin thickening and varying degrees of lichenification, including severe itching, tendency of persistence and recurrence with serious impact on quality of life of patients. Objective: To assess the clinical efficacy and safety of calcipotriol betamethasone ointment in patients with chronic eczema. Methods: In this multi-center, randomized, single-blind, positive drug parallel controlled clinical study, patients were randomly divided into treatment and control groups, to receive calcipotriol betamethasone ointment or halometasone/triclosan cream, respectively, once daily in the evening over a 4-week period. The safety and efficacy of the two regimens were followed up on weeks 1, 2, 4 and at a 4-week treatment-free period. According to the degree of improvement, the total scores (0-4) before and after treatment and the efficacy index were calculated. The overall efficacy was assessed by four levels of evaluation model. Results: After 4 weeks of treatment, the cure rate was high (44.70%) in treatment group compared with control group (15.56%) (P<0.001), and the effective rate was 83.33% and 55.56% in the respective groups (P<0.001). At 2 and 4 weeks after treatment, there was significant difference (P<0.05) between two groups, with a reduction in the intensity of pruritus, inflammation, infiltration/ hypertrophy, lichenification, and area of target lesions. The incidence of adverse events was more (1.52%) in treatment than control group (0.00%) (P>0.05). Conclusion: Calcipotriol betamethasone ointment appears to be a safe and effective option for the treatment of chronic eczema.